Board Games as a Game-Based Learning Strategy for Improving Maharah Kalam among Arabic Language Learners - Ibrahim Abdul Qohhar; Zainal Arifin Mukmin; Irmansyah Irmansyah (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2026)
This study aims to analyze the effectiveness of implementing the Game-Based Learning (GBL) method assisted by board game media in improving speaking skills (maharah kalam) of eighth-grade students at Sekolah Islam Terapan Prof. Muhajirin Palembang. This study employed a mixed-method approach, integrating a quasi-experimental design (pre-test and post-test) with qualitative methods The quantitative data were gathered from 20 eighth-grade students through pre-test and post-test speaking assessments scored using a four-criteria rubric (pronunciation, fluency, vocabulary, and comprehension), while qualitative data were collected through structured observation checklists, semi-structured interviews with two Arabic teachers and six students, and documentation, and speaking ability tests. The results showed that before the implementation of GBL, the students’ average pre-test score was 58.75, with low levels of motivation and engagement. After the application of GBL assisted by board games, the average post-test score significantly increased to 87.5. This improvement demonstrates that GBL is effective in enhancing Arabic speaking skills, while also boosting students’ motivation and active participation. These findings affirm that integrating the GBL method with board game media can serve as an innovative alternative in Arabic language learning at the junior high school level. These findings imply that Arabic language teachers should consider adopting game-based, interactive approaches to foster communicative competence, and that curriculum designers and school administrators can incorporate board game media as a structured and replicable pedagogical tool in Islamic junior high school settings.